Singapore clinical guideline on parenteral nutrition in adult patients in the acute hospital setting - Johnathan Huey Ming Lum; Hazel Ee Ling Yeong; Pauleon Enjiu Tan; Ennaliza Salazar; Tingfeng Lee; Yunn Cheng Ng; Janet Ngian Choo Chong; Pay Wen Wong; Jeannie Peng Lan Ong; Siao Ching Gooi; Kristie Huirong Fan; Weihao Chen; et al. (Annals, Academy of Medicine, Singapore)
Introduction: The primary objective of this guideline is to establish evidence-based recommendations for the clinical use of parenteral nutrition (PN) in adult patients within the acute hospital setting in Singapore. Method: An expert workgroup, consisting of healthcare practitioners actively involved in clinical nutrition support across all public health institutions, systematically evaluated existing evidence and addressed clinical questions relating to PN therapy. Results: This clinical practice guideline developed 30 recommendations for PN therapy, which cover these key aspects related to PN use: indications, patient assessment, titration and formulation of PN bags, access routes and devices, and monitoring and management of PN-related complications. Conclusion: This guideline provides recommendations to ensure appropriate and safe clinical practice of PN therapy in adult patients within the acute hospital setting.